Assessing the role of central lymph node ratio in predicting recurrence in N1a low-to-intermediate risk papillary thyroid carcinoma - Ma, Teng; Cui, Jian; Shi, Peng; Liang, Mei; Song, Wenxiao; Zhang, Xueyan; Wang, Lulu; Shi, Yafei (Frontiers in Endocrinology, 2023)
Introduction: Lymph node metastasis in patients with papillary thyroid carcinoma (PTC) is associated with postoperative recurrence. Recently, most studies have focused on the evaluation of recurrence in patients with late-stage PTC, with limited data on those with early-stage PTC. We aimed to assess the relationship between lymph node ratio (LNR) and recurrence in low-to-intermediate-risk patients and validate its diagnostic efficiency in both structural (STR) and biochemical recurrence (BIR). Methods: Clinical data of patients with PTC diagnosed at the Affiliated Hospital of Jining Medical University were retrospectively collected. The optimal LNR cut-off values for disease-free survival (DFS) were determined using X-tile software. Predictors were validated using univariate and multivariate Cox regression analyses. Results: LNR had a higher diagnostic effectiveness than metastatic lymph nodes in patients with low-to-intermediate recurrence risk N1a PTC. The optimal LNR cutoff values for STR and BIR were 0.75 and 0.80, respectively. Multivariate Cox regression analysis showed that LNR≥0.75 and LNR≥0.80 were independent factors for STR and BIR, respectively. The 5-year DFS was 90.5% in the high LNR (≥0.75) and 96.8% in low LNR (<0.75) groups for STR. Regarding BIR, the 5-year DFS was 86.9% in the high LNR (≥0.80) and 75.7% in low LNR (<0.80) groups. The high and low LNR survival curves exhibited significant differences on the log-rank test. Conclusion: LNR was associated with recurrence in patients with low-to-intermediate recurrence risk N1a PTC. We recommend prophylactic lateral cervical lymph node dissection and radioactive iodine ablation therapy for patients with high LNR (≥0.75).